2014
DOI: 10.1007/s00429-014-0963-x
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β disrupts ongoing spontaneous activity in sensory cortex

Abstract: both firing patterns and spike shape were changed in the APP/PS1 group. At the population level, LFP recordings indicated reduced coherence within neuronal assemblies of APP/PS1 mice. In addition to the physiological effects, we show that morphology of neurites within the barrel cortex of the APP/PS1 model is altered compared to CONTROLS. These results are consistent with a process where the effect of Aβ on spontaneous activity of individual neurons amplifies into a network effect, reducing network integrity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 45 publications
4
12
0
Order By: Relevance
“…***p < 0.001, Wilcoxon rank sum). Our results are in accordance with previous observations reported in studies using diverse strains of AD mice and various types of anesthesia 18 19 20 29 40 .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…***p < 0.001, Wilcoxon rank sum). Our results are in accordance with previous observations reported in studies using diverse strains of AD mice and various types of anesthesia 18 19 20 29 40 .…”
Section: Resultssupporting
confidence: 93%
“…Synchronous activity is a fundamental feature in the operation of large cortical networks 61 62 63 64 . It has been shown that Aβ accumulation and plaques disrupt the synchrony of convergent inputs and reduce the ability of neurons to successfully integrate and propagate information 10 29 . In AD patients, there are large number of evidence for reduced neural synchrony during the resting state 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the amyloid cascade hypothesis of AD pathogenesis (Hardy and Higgins, 1992 ), Aβ deposition in the brain triggers a series of events that ultimately leads to the development of the disease (Karran et al, 2011 ). For example, major downstream effects of Aβ deposition include synaptic and neuronal loss (Selkoe, 1991 ), as well as disruption to spontaneous activity of brain areas (Beker et al, 2014 ). This dysfunction is postulated to propagate to downstream neurons within the recurrent network (Beker et al, 2014 ), highlighting the idea that the olfactory system provides an ideal network for investigating mechanisms of AD pathogenesis.…”
Section: Insight Into Mechanisms Of Alzheimer’s Disease Pathogenesis mentioning
confidence: 99%
“…For example, major downstream effects of Aβ deposition include synaptic and neuronal loss (Selkoe, 1991 ), as well as disruption to spontaneous activity of brain areas (Beker et al, 2014 ). This dysfunction is postulated to propagate to downstream neurons within the recurrent network (Beker et al, 2014 ), highlighting the idea that the olfactory system provides an ideal network for investigating mechanisms of AD pathogenesis.…”
Section: Insight Into Mechanisms Of Alzheimer’s Disease Pathogenesis mentioning
confidence: 99%